PENGARUH KETERAMPILAN MENGAJAR GURU DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR SISWA MATA PELAJARAN EKONOMI DI SMAN 2 SIAK HULU KABUPATEN KAMPAR - H e l e n ' (PEKBIS, 2016)
This study aims to find out the influenceof teachers' teaching skills and learning motivation to student achievement of economic subjects in SMAN 2 Siak Hulu Kampar Regency. Method in this research is quantitative. The study population was the students of class XI IPS in SMAN 2 Siak Hulu Kampar Regency as 171 respondents and total sample are 63 respondents selected by random sampling technique. Data obtained by observing the teacher in class and distributing questionnaires to respondens. Data analyzed using Path Analysis. Test the instrument test the validity and reliability using alpha cronbach. Result showed that: (1) a significant effect the teachers' teaching skills to learn motivation economic subjects in SMAN 2 Siak Hulu Kampar, (2) there are significant effect teachers' teaching skills and learn motivation either directly or indirectly to student achievement of economic subjects in SMAN 2 Siak Hulu Kampar, and together the two independent variables contributed as much as 41.3% on student achievement and the remaining 58.7 % contributed by other factors beyond the teachers' teaching skills, such as socio-economic parents, abilities, interests and others. From these results it can be concluded that in order to improve student achievement can be done by improving the teaching skills of the teachers who taught economics.